ANALYSIS OF REGIONAL FINANCIAL MANAGEMENT AND MINIMUM WAGES ON INCOME DISTRIBUTION INEQUALITY IN EAST JAVA - Vena Tri Pramita; Kiky Asmara; Fauzatul Laily Nisa (JURNAL PROFIT, 2025)
Economic development is a transformation process aimed at improving public welfare, but it often creates income distribution inequality that becomes a major challenge for both developed and developing countries. Regional financial management that applies the value for money concept can drive economic growth, thereby enhancing public welfare. Therefore, each region strives to achieve quality and equitably distributed economic development to address various existing socio-economic problems.This study aims to analyze terrelationship between fiscal decentralization as the degree of fiscal decentralization, Gros Regional Domestic Product (GRDP) at constant prices based on business fields, and minimum wages on income disteution inequality in East Java Province for the period 2009-2023. Time series data were obtained from the Central Statistics Agency and the Directorate General of Fiscal Balance, then analyzed using multiple linear regression method with the assistance of EViews version 12 software. The research results show that collectively, the vertables of fiscal decentralization, GRDP at constant prices based on business fields, and minimum wages significantly influence incomelistribution inequality. However, when examined partially, figgl decentralization has a positive and non-significant effect, GRDP constant prices has a positive and significant effect, while minimum wages have a positive and non-significant effect on income distribution inequality in East Java Province